Particle placement and sheet topological control in the fabrication of Ag-hexaniobate nanocomposites - Adireddy, Shiva (Langmuir : the ACS journal of surfaces and colloids, 2015)
Synthetic methods are demonstrated that allow for the fabrication of Ag-hexaniobate nanocomposites with directed nanoparticle (NP) placement and nanosheet morphological control. The solvothermal treatment of exfoliated nanosheets (NSs) in the presence of Ag NPs leads to a high yield of Ag nanocomposites. This approach is quite flexible and, with control of time and temperature, can be used to produce nanocomposites with specific architectures; Ag NPs can be attached to nanosheets, attached to the surfaces of nanoscrolls, or at higher temperatures, captured within nanoscrolls to form nanopeapod (NPP) structures. The decorated nanosheets and nanoscrolls show surface plasmon resonance (SPR) maxima similar to that of free Ag NPs, while the Ag NPPs exhibit a red shift of about 10 nm